A review of the genus Metalype Klapálek, with descriptions of three new species from China (Trichoptera, Psychomyiidae) - Qiu, Shuang (Zookeys, 2017)
Abstract. Three new species of Metalype from China, Metalype hubeiensis Qiu & Morse, sp. n., Metalype shexianensis Qiu & Morse, sp. n., and Metalype truncata Qiu & Morse, sp. n., are described and illustrated. Metalype uncatissima (Botosaneanu, 1970) is reported from China for the first time. The differences between genus Metalype and genus Psychomyia are discussed and four Psychomyia species are transferred to Metalype: Metalype holzenthali (Schmid, 1997); Metalype klapaleki (Malicky, 1995a); Metalype kumari (Schmid, 1997); and Metalype nithaiah (Malicky, 2014). A key to the males of Metalype species of the world is provided.